The Role of Strategic Planning in Achieving Institutional Excellence within Public Organizations in the State of Qatar: the Case of the Ministry of Endowments and Islamic Affairs - Almaadeed, Noor A. Arhman; Almaweri, Ahmed Mohammed (The Arab Journal of Administration, 2025)
The study aimed at identifying the role of strategic planning in achieving institutional excellence within public organizations in the State of Qatar, with a specific focus on the Ministry of Endowments and Islamic Affairs. To achieve its objectives, the study adopted a qualitative approach relied on reviewing previous literature and official documents and conducting personal interviews with several administrative leaders in the ministry, who possess knowledge and expertise on the topic. The findings reveal that there is an effective and prominent role for strategic planning in achieving institutional excellence in the Ministry, which was clearly demonstrated through the contribution of strategic planning in achieving the four dimensions of the governmental excellence award in the State of Qatar, which are: the entrepreneurial orientation, the qualitative value, the institutional resources, in addition to the results and impact. The study emphasized the importance of raising awareness among members of public organizations, in the State of Qatar at all levels, regarding institutional excellence and the award’s themes, as it was recently announced, which requires further understanding. Moreover, the study highlighted the need to align strategic planning efforts in a way that contributes to achieving the governmental excellence in line with Qatar National Vision 2030.